Analisis Yuridis Penyelesaian Gugatan Pembatalan Sk Bupati Bangkalan Terkait Penetapan Kepala Desa Banyuajuh - Robby Destami Sudirman (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this research is to understand the mechanism of dispute resolution resulting from the election of the head of Banyuajuh Village in Bangkalan Regency, with a focus on the conformity of legal considerations in the PTUN Surabaya decision number 155/G/2021/PTUN.SBY with the applicable laws and regulations. The author uses normative research method and library research approach to gather legal materials, including sources from experts, research findings, and journals related to the mechanism of dispute resolution based on the laws and regulations.